Early withdrawal of life support after resuscitation from cardiac arrest is common and may result in additional deaths. (June 2019) - May, Teresa L.; Ruthazer, Robin; Riker, Richard R.; Friberg, Hans; Patel, Nainesh; Soreide, Eldar; Hand, Robert; Stammet, Pascal; Dupont, Allison; Hirsch, Karen G.; Agarwal, Sachin; Wanscher, Michael J.; et al.
Abstract: Aim: "Early" withdrawal of life support therapies (eWLST) within the first 3 calendar days after resuscitation from cardiac arrest (CA) is discouraged. We evaluated a prospective multicenter registry of patients admitted to hospitals after resuscitation from CA to determine predictors of eWLST and estimate its impact on outcomes. Methods: CA survivors enrolled from 2012–2017 in the International Cardiac Arrest Registry (INTCAR) were included. We developed a propensity score for eWLST and matched a cohort with similar probabilities of eWLST who received ongoing care. The incidence of good outcome (Cerebral Performance Category of 1 or 2) was measured across deciles of eWLST in the matched cohort. Results: 2688 patients from 24 hospitals were included. Median ischemic time was 20 (IQR 11, 30) minutes, and 1148 (43%) had an initial shockable rhythm. Withdrawal of life support occurred in 1162 (43%) cases, with 459 (17%) classified as eWLST. Older age, initial non-shockable rhythm, increased ischemic time, shock on admission, out-of-hospital arrest, and admission in the United States were each independently associated with eWLST. All patients with eWLST died, while the matched cohort, good outcome occurred in 21% of patients. 19% of patients within the eWLST group were predicted to have a good outcome, had eWLST not occurred. Conclusions: Early withdrawal of life support occurs frequently after cardiac arrest. Although the mortality of patients matched to those with eWLST was high, these data showed excess mortality with eWLST.